Transcriptome-wide analysis of trigeminal ganglion and subnucleus caudalis in a mouse model of chronic constriction injury-induced trigeminal neuralgia - Cui, Xiaona; Qin, Bo; Xia, Chaoyun; Li, Hong; Li, Zhiye; Li, Zhisong; Nasir, Abdul; Bai, Qian (Frontiers in Pharmacology, 2023)
Trigeminal neuropathic pain (TNP) induces mechanical allodynia, and hyperalgesia, which are is known to alter gene expression in injured dorsal root ganglia primary sensory neurons. Non-coding RNAs (ncRNAs) have been linked to TNP. However, the functional mechanism underlying TNP and the expression profile of ncRNAs in the trigeminal ganglion (TG) and trigeminal subnucleus caudalis (Sp5C) are still unknown. We used RNA-sequencing (RNA-seq) and bioinformatics analysis to examine the TG and Sp5C transcriptomes after infraorbital nerve chronic constrictive injury (IoN-CCI). The robust changes in gene expression of lncRNAs, circRNAs and mRNAs within the TG and Sp5C from mice that underwent IoN-CCI and the sham-operated mice (day 7). In total, 111,003 lncRNAs were found in TG and 107,157 in Sp5C; 369 lncRNAs were differentially expressed in TG, and 279 lncRNAs were differentially expressed in Sp5C. In addition, 13,216 circRNAs in TG and 21,658 circRNAs in Sp5C were identified, with 1,155 circRNAs and 2,097 circRNAs differentially expressed in TG and Sp5C, respectively. Furthermore, 5,205 DE mRNAs in TG and 3,934 DE mRNAs in Sp5C were differentially expressed between IoN-CCI and sham groups. The study revealed a high correlation of pain-related differentially expressed genes (DEGs) in the TG and Sp5C to anxiety, depression, inflammation, neuroinflammation, and apoptosis. GO analysis revealed that binding-related molecular functions and membrane-related cell components were significantly enriched. KEGG analysis shows the most significant enrichments in neurogenesis, nervous system development, neuron differentiation, adrenergic signalling, cAMP signalling, MAPK signalling, and PI3K-Akt signalling pathways. Furthermore, PPI analysis showed that hub genes were implicated in neuropeptide signalling pathways. Functional analysis of DE ncRNAs Targeting Genes was mostly enriched with nociception-related Signaling pathways underpinning TNP. Our findings suggest that ncRNAs are involved in TNP development and open new avenues for research and treatment.